Financial Reporting Quality and External Debt Financing Constraints: The Case of Privately Held Firms. (12th August 2016) - Ding, Shujun; Liu, Mingzhi; Wu, Zhenyu
Abstract : Using a sample consisting of 1, 160, 801 observations of privately held firms, we explore the relationship between earnings quality and privately held firms' debt financing, access to debt, and cost of debt, as well as the moderating effects of provincial‐level economic development on this relationship. Our findings indicate that better earnings quality increases private firms' access to debt financing and lowers their cost of debt. The empirical results also show that these effects are more pronounced in less developed provinces.